The Influence of Financial Report Quality, Profitability and Tax Avoidance Practices on Business Value Through Financial Performance as a Mediating Variable in Banking Sector Companies - Yusuf Jaya Sumantri; Andri Zainal; Azizul Kholis (Randwick International of Social Science Journal, 2024)
This research analyzes the influence of financial report quality, profitability, tax avoidance practices on financial performance; analyze the influence of financial report quality, profitability, tax avoidance practices on business value; and analyzing financial performance in mediating the relationship between financial report quality, profitability and tax avoidance practices and business value. The research sample was 20 (twenty) financial reports from 6 (six) banking companies listed on the Indonesia Stock Exchange (BEI) for the period 2017 to 2022, namely BNI, BRI, Bank Danamon, BCA, Bank CIMB Niaga and Bank Permata with 79 observations. The data collection technique was showed by accessing the official PT website. Indonesia stock exchange. The data analysis technique is path analysis with correlation and regression techniques. The research results show that the quality of financial reports has no effect on business performance; profitability influences business performance; tax avoidance practices have no effect on business performance; the quality of financial reports has no effect on business value; profitability influences the value of banking companies; tax avoidance practices have no effect on business value; financial performance has no effect on the value of banking companies; financial performance cannot mediate the relationship between financial report quality and business value; financial performance cannot mediate the relationship between profitability and firm value; and between tax avoidance practices and firm value.